Power loss assessment in polymer and ceramic insulators due to aging: an experimental study - Basit Alia; Kaniz Fatima; Arman Nadeem; Saud Alid; Usama Zakir (Penerbit Universiti Kebangsaan Malaysia, 2024)
The objective of this study is to analyze the influence of smog on polymer and ceramic insulators, which can lead to flashovers in the distribution network. An experimental chamber was designed to conduct an aging test on the insulators, where in the chamber was subjected to five different types of artificial environments, including rain, temperature, smog, and dust. The chamber was set to replicate the environmental conditions of a smoggy region based on the last five years data for all environmental factors, such as rain, temperature, humidity, smog, and dust. The accelerated aging test was conducted on 11KV-rated polymer and ceramic insulators. The polymer insulator developed contamination of 0.09 gm, while the ceramic insulator showed contamination of 0.13 gm. Furthermore, a leakage current test was performed on the aged insulators, which resulted in 37uA on the polymer insulator and 201uA on the ceramic insulator. The findings suggest that ceramic insulators are more susceptible to the adverse effects of a smoggy environment compared to polymer insulators. Thus, replacing ceramic insulators with polymer insulators in the distribution network not only reduce losses due to the leakage current but it also improve the cost of installation of new distribution networks that can improve the network’s reliability.